Reliability and Validity of the Measurement of Scapular Position Using the Protractor Method. Issue 4 (1st April 2016) - O'Shea, Aidan; Kelly, Rory; Williams, Sian; McKenna, Leanda
Abstract : Background: The protractor method is a proposed clinical assessment tool, the first to measure vertical scapular position, that directly compares scapular and spinal landmarks. This tool has the potential to reliably and accurately measure excessive scapular elevation or depression. Objective: The purpose of this study was to determine reliability and validity of the protractor method to measure resting scapular position. Design: An interrater and intratester reliability and validity study was conducted. Methods: Testing was conducted on the same day by 2 physical therapists who were blinded to each other's results. The vertical distances between the spinous process of C7 and the superior margin of the medial aspect of the spine of the scapula (C7 method) and the spinous process of T8 and the inferior angle of the scapula (T8 method) were palpated and measured on the symptomatic shoulder in 34 people with current shoulder pain using the protractor method. Measurements were compared with 2-dimensional camera analysis to assess validity. Results: For intertester reliability, the standard error of measure, minimal detectable change, and intraclass correlation coefficient were 6.3 mm, 17.3 mm, and .78, respectively, for the C7 method and 5.7 mm, 15.7 mm, and .82, respectively, for the T8 method. For intratester reliability, the standard error of measure, minimal detectable change, and intraclass correlation coefficient were <0.9 mm, <2.5 mm, and .99, respectively. For validity, significant correlations ( r ) and mean differences were .83 and 10.1 mm, respectively, for the C7 method and .92 and 2.2 mm, respectively, for the T8 method. Limitation: The results of this study are limited to static measurement of the scapula in one plane. Conclusion: Both protractor methods were shown to have good reliability and acceptable validity, with the T8 method demonstrating superior clinical utility. The clinical use of the T8 method is recommended for measurement of excessive resting scapular elevation or depression.